Pancreatic Panniculitis: A Rare Presentation Case: Paniculite Pancreática: Forma de Apresentação Rara - Monteiro, Eunice Vieira e; Munhoz, Ana; Paiva, Cláudia; Soares, Paulo Aguiar (Gazeta Médica, 2020)
A 46-year-old man with a personal history of kidney transplantation in 1994 for reflux nephropathy with chronic graft dysfunction.